2003
DOI: 10.1248/bpb.26.845
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Quantitative Analysis of Cryptotanshinone, an Active Quinoid Diterpene Formed in Callus of <i>Salvia miltiorrhiza</i> B<small>UNGE</small>

Abstract: Effect of N(6)-benzyladenine (BA) on tanshinone formation in callus cultures of Salvia miltiorrhiza was examined in an attempt to increase the productivity of the medicinal compound, cryptotanshinone. Primary callus was induced by culturing leaf explants on Murashige and Skoog's (MS) basal medium supplemented with 1.0 mg l(-1) of 2,4-dichlorophenoxyacetic acid (2,4-D) in darkness. The callus proliferated further on MS basal medium containing 1.0 mg l(-1) 2,4-D and 0.5 mg l(-1) BA and was analyzed for cryptotan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 35 publications
0
21
1
Order By: Relevance
“…In previous studies, in vitro methods such as hairy root cultures (Hu et al 1993; Ge and Wu 2005a; Yan et al 2005), cell suspension cultures (Chen et al 1997), addition of elicitors and optimization of media (Wu et al 2003; Zhang et al 2004; Ge and Wu 2005b; Gupta et al 2011), have been reported. In our previous study, ATM transgenic callus lines of Salvia with greater tanshinones content were developed (Lee et al 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies, in vitro methods such as hairy root cultures (Hu et al 1993; Ge and Wu 2005a; Yan et al 2005), cell suspension cultures (Chen et al 1997), addition of elicitors and optimization of media (Wu et al 2003; Zhang et al 2004; Ge and Wu 2005b; Gupta et al 2011), have been reported. In our previous study, ATM transgenic callus lines of Salvia with greater tanshinones content were developed (Lee et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…miltiorrhiza has been studied by various research groups over the world, especially in biotechnological and in vitro propagation field. Through several strategies like genetic manipulation of biosynthetic pathway via genetic transformation (Chen et al 1997; Lee et al 2008; Kai et al 2011), hairy root cultures (Hu et al 1993), use of plant growth regulators and elicitors (Wu et al 2003; Zhang et al, 2004; Ge and Wu 20052005; Gupta et al 2011), success has been reported in enhancing the production of secondary metabolites in S. miltiorrhiza .…”
Section: Introductionmentioning
confidence: 99%
“…The dried root of Dan‐shen (Radix Salvia miltiorrhizae ) is one of the most popular traditional Chinese herbal medicines and has been widely used for the treatment of menstrual disorders, menorrhealgia, insomnia, menostasis, blood circulation diseases, and other cardiovascular diseases 1–9. Many studies of its chemical constituents have been reported 10–16. Depending on their chemical structures, the major bioactive constituents can be classified into two major groups: water‐soluble phenolic compounds and nonpolar diterpenoid compounds.…”
mentioning
confidence: 99%
“…CTS (purity Ͼ99%, as determined by thin-layer chromatography) and tanshinone IIA (purity Ͼ95%, as determined by thin-layer chromatography) were extracted and purified from the root of S. miltiorrhiza using the CH 2 Cl 2 method as described previously (Hur et al, 2005) at the School of Pharmaceutical Sciences, Sun Yat-sen University, Guangzhou, People's Republic of China. CTS and tanshinone IIA were identified by comparison of liquid chromatography-mass spectrometry and nuclear magnetic resonance spectral data with reference values (Wu et al, 2003). Phenol red was purchased from Tianjin Chemical Reagents Institute (Tianjin, People's Republic of China).…”
Section: Methodsmentioning
confidence: 99%